Identification of a fungi-specific lineage of protein kinases closely related to tyrosine kinases. - Zhongtao Zhao; Qiaojun Jin; Jin-Rong Xu; Huiquan Liu (PLoS ONE)
Tyrosine kinases (TKs) specifically catalyze the phosphorylation of tyrosine residues in proteins and play essential roles in many cellular processes. Although TKs mainly exist in animals, recent studies revealed that some organisms outside the Opisthokont clade also contain TKs. The fungi, as the sister group to animals, are thought to lack TKs. To better understand the origin and evolution of TKs, it is important to investigate if fungi have TK or TK-related genes. We therefore systematically identified possible TKs across the fungal kingdom by using the profile hidden Markov Models searches and phylogenetic analyses. Our results confirmed that fungi lack the orthologs of animal TKs. We identified a fungi-specific lineage of protein kinases (FslK) that appears to be a sister group closely related to TKs. Sequence analysis revealed that members of the FslK clade contain all the conserved protein kinase sub-domains and thus are likely enzymatically active. However, they lack key amino acid residues that determine TK-specific activities, indicating that they are not true TKs. Phylogenetic analysis indicated that the last common ancestor of fungi may have possessed numerous members of FslK. The ancestral FslK genes were lost in Ascomycota and Ustilaginomycotina and Pucciniomycotina of Basidiomycota during evolution. Most of these ancestral genes, however, were retained and expanded in Agaricomycetes. The discovery of the fungi-specific lineage of protein kinases closely related to TKs helps shed light on the origin and evolution of TKs and also has potential implications for the importance of these kinases in mushroom fungi.